Integrative-Interconnective Approach In Sets: A Teaching Material Development for Enhancing Students' Conceptual Understanding - Fahrudin, Fadrik Adi; Indah Setyo Wardhani (Universitas Pendidikan Ganesha, 2025)
The low level of student understanding and the limited teaching materials that can link set theory with Islamic values are one of the main obstacles in mathematics learning at the madrasah level. This study aims to develop teaching materials in the form of modules and student worksheets (SW) based on an integrative-interconnected approach to address students' difficulties in understanding set concepts. This research is a research and development (R&D) study following the ADDIE model, with stages including initial analysis, prototype development, and product validation. The subjects of this study were junior high school students. Data were collected through document analysis, questionnaires, and tests, and analyzed using descriptive quantitative methods. Validation results indicated that the instructional materials had a high level of feasibility, both in terms of content and media. Students' responses to the modules and worksheets were categorized as good to very good, and classical learning achievement showed a significant improvement. These findings indicate that the developed teaching materials are effective in improving students' understanding of set theory. The implications of this study suggest that the integrative-interconnected approach can serve as an alternative strategy for developing contextual teaching materials relevant to religious values.